Soft magnetic geopolymer in airport pavement induction heating: Effect of Fe powder distribution on the electromagnetic loss. Issue 2 (15th January 2023) - Gu, Gonghui; Ma, Tao; Chen, Feng; Li, Heng; Pei, Yaowen; Xu, Fang
Abstract: During the induction heating of airport pavement to melt snow and ice, soft magnetic geopolymer can shape magnetic field distribution and enhance energy utilization efficiency by reducing potential electromagnetic loss. The goal of this study is to investigate the effect of Fe powder distribution on the electromagnetic loss of soft magnetic geopolymer during airport pavement induction heating. The findings can provide theoretical guidance for the design of soft magnetic geopolymer layer used in airport pavement induction heating. The following are the key findings from this study: (1) A force model suitable for studying the flow of iron powder in fresh geopolymer paste was proposed, which can be used to predict and control the movement and distribution of iron powder within the geopolymer paste during the curing process; (2) The low static yield stress of fresh geopolymer paste can result in a non-zero resultant force acting on the iron powder inside the soft magnetic geopolymer, causing the iron powder to move downward and deposit; (3) Iron powder sedimentation should be avoided because it can intensify magnetic and electrical coupling between particles, resulting in significant polarization loss and eddy current loss inside the soft magnetic geopolymer, and lowering induction heating efficiency.